Islamic Patience Exercises to Reduce Delinquency in Adolescents Viewed from Parenting Patterns - Risydah Fadilah; Setiawati Intan Savitri; Laili Alfita; Sari Atika Parinduri, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The delinquency problem is increasing significantly worldwide. Mainly, delinquency in adolescents is growing rapidly, causing several issues in societies. Similar to other countries, delinquency among adolescents in Indonesia is increasing. The current study attempted to examine the role of Islamic patience exercise in the failure of adolescents in Indonesia to address this problem. Furthermore, the part of parental education is also considered to explore this relationship. A survey is carried out among the Indonesian schools to collect primary data. Questionnaires were distributed among the teachers in Indonesian schools. It is found that; Islamic education has central importance in controlling delinquency in adolescents. Islamic education in schools can promote spiritual knowledge and social awareness. The promotion of spiritual knowledge and social understanding further led to decreased delinquency. Additionally, parental education has vital importance in reducing negligence. Parental education at the household level can decrease failure in adolescents. This study provided several implications for the management of schools, parents, and crime control authorities to reduce delinquency in adolescents by promoting Islamic education.